In splendid isolation : a history of the Willie Commelin Scholten Phytopathology Laboratory 1894-1992 - Faasse, Patricia (History of science and scholarship in the Netherlands, 2008)
Compared to a sick human being, a diseased plant is a simple object. You can cut it into pieces, examine parts of it under a microscope and perform all sorts of experiments with it, without the need for physical precautions or compassion. In other respects, however, physicians who deal with human diseases have an easy life. 'You physicians have only one species of patient, we phytopathologists have hundreds. Today we might be looking at a lily-of-the-valley, tomorrow an elm tree, the next day Java coffee, ' explains one of the phytopathologists in this book. For almost a hundred years, the Will.